Assessing the sensitivity of inflation to economic activity - Konstantins Benkovskis; Michele Caivano; Antonello D'Agostino; Alistair Dieppe; Samuel Hurtado; Tohmas Karlsson; Eva Ortega; Tímea Várnai (European Central Bank (ECB), 2011)
A number of academic studies suggest that from the mid-1990s onwards there were changes in the link between inflation and economic activity. However, it remains unclear the extent to which this phenomenon can be ascribed to a change in the structural relationship between inflation and output, as opposed to a change in the size and nature of the shocks hitting the economy. This paper uses a suite of models, such as time-varying VAR techniques, traditional macro models, as well as DSGE models, to investigate, for various European countries as well as for the euro area, the evolution of the link between inflation and resource utilization and its dependence on the nature and size of the shocks. Our analysis suggests that the relationship between inflation and activity has indeed been changing over time, while remaining positive, with the correlation peaking during recessions. Quantitatively, the link between output and inflation is found to be highly dependent on which type of shocks hit the economy: while, in general, all demand shocks to output imply a reaction of inflation of the same sign, the latter will be less pronounced when output fluctuations are driven by supply shocks. In addition, a sharp deceleration of activity, as opposed to a subdued but protracted slowdown, results in a swifter decline in inflation. Inflation exhibits a rather strong persistence, with a negative impact still visible three years after the initial shock.
Keywords: E31; E32; E37; 330; demand shock; inflation response; Macro model; output growth; Phillips curve